Template-free, controllable and scalable synthesis of poly(5-aminoindole) nanoparticles for printable electrochemical immunosensor with ultra-high sensitivity. Issue 1 (30th November 2021) - Yang, Taotao; Rao, Ai; Liang, Yao; Yang, Kun; Ye, Yongqin; Ren, Xiaoning; Wang, Bin; Luo, Zhiqiang
Abstract : The PIn-5-NH2 NPs possess distinct features, including good conductivity, large surface area, and abundant –NH2 functional groups for covalent binding of the antibody, and therefore offer substantial possibilities for developing an all-printable process to fabricate multiplexed electrochemical immunosensors. Abstract : Conductive polymer polyindole derivatives have good conductivities and abundant functional groups, which would offer great potential for versatile applications including biosensors, bioelectronics and energy devices. However, the polyindole derivatives are mainly synthesized by the electropolymerization method on conductive electrode surfaces, which limits large-scale synthesis and practical applications. Herein, we explore a strategy of template-free, controllable and scalable synthesis of poly-5-aminoindole (PIn-5-NH2 ) nanoparticles (NPs) and demonstrate the application of PIn-5-NH2 NPs in printable multiplexed electrochemical biosensors with ultra-high sensitivity. The synthesis of PIn-5-NH2 NPs is based on a self-templated method since the In-5-NH2 monomer with amphiphilic structures can form micelles by self-assembly in an aqueous solution. The diameter of PIn-5-NH2 NPs could be controlled by adjusting the synthesis conditions, such as monomer concentration, oxidant/monomer ratio and reaction time. The PIn-5-NH2 NPs possess distinct features, including good conductivity, large surface area, and abundant –NH2 functional groups for covalent binding of the antibody, and therefore offer substantial possibilities for developing an all-printable process to fabricate multiplexed electrochemical immunosensors. The printed multiplexed electrochemical immunosensors on the basis of the aqueous suspension of PIn-5-NH2 NPs linked with antibodies can simultaneously detect multiple cancer markers, and exhibit high sensitivity and good selectivity. Our facile and scalable synthesis strategy would offer great opportunities for versatile applications of PIn-5-NH2 NPs.